INFLUENCE OF TEACHERS’ ATTITUDE ON IMPLEMENTATION OF LANGUAGE OF INSTRUCTION POLICY. - Omweri, Martha Nyaboke; Juliet, Dr.Mugo,W. (IJRDO- Journal of Educational Research, 2017)
The purpose of the study was to investigate on implementation of the language of instruction policy in pre-unit and lower primary classes in Kasarani, Nairobi County, Kenya. The need to carry out the study arose from the growing concern by various researchers that using the language of the catchment area (LOCA) or mother tongue (MT) as a medium of instruction in lower primary classes had been displaced by English. This is in spite of the research findings that language of the catchment area is crucial to the learning process. Specifically the purpose of the study was to determine the teachers’ attitude on the implementation of language of instruction policy in preunit and lower classes and suggest interventions to enhance its implementation. The researcher adopted a descriptive research design, using the survey method. All the l50 lower primary schools within the division, their head teachers/directors, 600 class teachers and 900 parents formed the target population of the study. The research was carried out on a sample of 45 (30%) primary schools which were randomly selected according to strata, their head teachers, 90 teachers and a similar number of parents. Data was collected using questionnaires and interview schedules. Prior to the study, piloting was conducted in five schools (two public and three private). Both quantitative and qualitative research methods were used to analyze data. Specifically, quantitative data was analyzed using descriptive analysis and data exploration. Preliminary reports and conclusions were based on descriptive statistics mainly frequencies and percentages and presented using charts, figures and text. Qualitative data were organized in themes and reported according to the research questions. Language of instruction determines the quality of education and therefore should be a language which is understandable to both learners and teachers. The study revealed that although majority of teachers were aware of the language policy and supported the use of language of catchment area for instruction, they were not using it because they found itchallenging to use to teach all subjects. Some of the suggestions made for intervention included: stepping up awareness of this policy to parents and teachers, training of teachers and in-servicing